Sistem Informasi Akademik (SIAKAD) SMP Negeri 1 Pajar Bulan Berbasis Web - Desi Puspita (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2017)
The purpose of this research is to design and make Academic Information System (SIAKAD) SMP Negeri 1 Pajar Bulan web-based, based on the preliminary study of researchers SMP Negeri 1 Pajar Bulan Lahat District in data processing has been computerized by using Microsoft Word and Exel programming but Do not have a better system like Academic Information System. System development method used is web engineering in stages include: Customer communication, Planning, Modeling, Contruction and Deployment. Designing using Unified Modeling Languange (UML), programming using PHP and MySql. Results peneilitian the Academic Information System SMP Negeri 1 Pajar Bulan Based Web.